Modeling and Process Operability Analysis o f a Di rec t A i r Ca p t ure System. Issue 7 (2022) - Gama, Vitor V.; Dinh, San; Alves, Victor; Dantas, Beatriz N.A.; Bishop, Brent A.; Lima, Fernando V.
Abstract: The climate crisis has become an important subject of study since it has impacted every single life on the planet. Aggravated by the large amounts of carbon dioxide released to the atmosphere, such crisis has influenced environmental regulations around the world. To lower the accumulation of this greenhouse gas in the atmosphere, several new technologies are currently being explored in the field of carbon capture and sequestration. This research focuses primarily on Direct Air Capture (DAC) technologies since they have advantages such as ease in installing and placing their facilities. Thus, the capture could be carried out near energy sources and storage sites, hence reducing costs and emissions especially of geographically remote CO2 producing processes. The DAC system design can be customized to meet the desired CO2 specifications in the captured product. In this work, a 3-stage membrane module arrangement for DAC is chosen due to its CO2 separation capabilities. A novel framework based on operability analysis is also employed to find a feasible design region for the DAC system that can operate at different pollution levels. The system is simulated employing AVEVA Process Simulation (an equation-oriented software) coupled with a Python script interface as well as MATLAB to perform process operability calculations. The results show that a feasible design for DAC can be successfully established with the proposed framework accounting for product and byproduct impurities.